New insights into the mineralogy of the Atlantis II Deep metalliferous sediments, Red Sea. (31st December 2015) - Laurila, Tea E.; Hannington, Mark D.; Leybourne, Matthew; Petersen, Sven; Devey, Colin W.; Garbe‐Schönberg, Dieter
Abstract: The Atlantis II Deep of the Red Sea hosts the largest known hydrothermal ore deposit on the ocean floor and the only modern analog of brine pool‐type metal deposition. The deposit consists mainly of chemical‐clastic sediments with input from basin‐scale hydrothermal and detrital sources. A characteristic feature is the millimeter‐scale layering of the sediments, which bears a strong resemblance to banded iron formation (BIF). Quantitative assessment of the mineralogy based on relogging of archived cores, detailed petrography, and sequential leaching experiments shows that Fe‐(oxy)hydroxides, hydrothermal carbonates, sulfides, and authigenic clays are the main "ore" minerals. Mn‐oxides were mainly deposited when the brine pool was more oxidized than it is today, but detailed logging shows that Fe‐deposition and Mn‐deposition also alternated at the scale of individual laminae, reflecting short‐term fluctuations in the Lower Brine. Previous studies underestimated the importance of nonsulfide metal‐bearing components, which formed by metal adsorption onto poorly crystalline Si‐Fe‐OOH particles. During diagenesis, the crystallinity of all phases increased, and the fine layering of the sediment was enhanced. Within a few meters of burial (corresponding to a few thousand years of deposition), biogenic (Ca)‐carbonate was dissolved, manganosiderite formed, and metals originally in poorly crystalline phases or in pore water were incorporated into diagenetic sulfides, clays, and Fe‐oxides. Permeable layers with abundant radiolarian tests were the focus for late‐stage hydrothermal alteration and replacement, including deposition of amorphous silica and enrichment in elements such as Ba and Au. Key Points: Atlantis II muds are chemical‐clastic sediments with distinctive fine layering that is mainly diagenetic in origin Fe‐(oxy)hydroxides, hydrothermal carbonates, sulfides, and authigenic clays are the main "ore" minerals Sequential leaching indicates nanophase hematite and nonsulfidic compounds are important components